From Seeing to Perceiving: The Audiovisual Construction and Embodied Experience of Rural Space in Documentaries - Qu, Lei; Teo, Miaw Lee; Candida, Jau Emang (Paradigm Academic Press, 2025)
This paper discusses some recent Chinese documentaries with rural themes. These documentaries use audiovisual codes to help audiences move from “seeing” spaces physically to “sensing” multidimensional spaces, triggering embodied experiences. Owing to a general tendency to focus on “what kind of space is depicted” in documentaries, scholars have systematically neglected the basic link of “how they trigger audiences’ sensory experiences”. Taking some recent documentaries including Remembering Nostalgia and Beautiful Countryside as examples, this paper intends to argue that there is a central argument in these documentaries: That is, documentaries “guide” viewers visually and “envelop” them aurally, making them an attractive textual body. That is, first, visually, mobile shots “guide” audiences to experience space as if they were “walking”, close-ups “stimulate” audiences to feel emotions, and changes in lighting effect create spatial atmosphere, which turn viewers from merely “seers” of spaces into active “explorers” of spaces. Second, aurally, a carefully designed soundscape and affective voice-over create a surrounding acoustic space that “envelops” audiences. In sum, the entire audiovisual strategy not only depicts images of countryside, but also effectively “mobilizes” viewers’ bodily memories and affective feelings to trigger embodied experiences, that is, “being there”. By exploring the sensory aesthetics and experiential construction in documentaries, this paper reveals how documentaries can help audiences leap from “seeing” spaces to “sensing”. Keywords: audiovisual construction, embodied experience, rural space, sensory aesthetics, Chinese documentaries